PENERAPAN MEDIA TEKA-TEKI PINTAR (TTP) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA PADA PERKALIAN DAN PEMBAGIAN KELAS 3 SD NEGERI DRINGU - Komaria Aziza; Didit Yulian Kasdriyanto; Faridahtul Jannah (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2023)
This study aims to determine the Increase in Activity and Learning Outcomes of Grade 3 Students of Dringu Public Elementary School in learning Mathematics in multiplication and division by using the Smart Puzzle (TTP) media. The number of grade 3 students consisted of 25 students with details of 10 male students and 15 female students. This type of research was Classroom Action Research which was carried out in 2 cycles while the stages in conducting this research included the planning stage, implementation, observation, and reflection. Data collection was obtained through interviews, observation, tests and documentation techniques. The data obtained in the Student Learning Outcomes study increased after applying the Smart Puzzle (TTP) media, which can be seen from the results of the students' pre-action, namely only 6 students (24%) got a complete score and 19 students (76%) got an incomplete score. In cycle 1 there was a slight increase, that is, 15 students (60%) got a complete score and 10 students (40%) got an incomplete score. The results of observations of teacher activities in cycle I obtained a value of 83.3 while the results of observations of student activities obtained a value of 79.5. In cycle 2 there was also an increase in learning outcomes, namely there were 22 students (88%) getting a complete score and 3 students (12%) getting an incomplete score. The results of observations of teacher activities in cycle II obtained a value of 97 while the results of observations of student activities obtained a value of 88.6. Thus it can be concluded that the Application of Smart Puzzle Media (TTP) can Increase the Activity and Learning Outcomes of Mathematics in the multiplication and division of Class 3 Students of SD Negeri Dringu. Abstrak Penelitian ini bertujuan untuk mengetahui Peningkatan Aktivitas dan Hasil Belajar Siswa Kelas 3 SD Negeri Dringu dalam pembelajaran Matematika pada perkalian dan pembagian dengan menggunakan media Teka-Teki Pintar (TTP). Adapun jumlah siswa kelas 3 terdiri dari 25 siswa dengan rincian siswa laki-laki berjumlah 10 dan siswi perempuan berjumlah 15. Jenis penelitian ini adalah Penelitian Tindakan Kelas (Classroom Action Research) yang dilaksanakan dalam 2 siklus adapun tahapan dalam melakukan penelitian ini meliputi tahap perencanaan, pelaksanaaan, observasi, dan refleksi. Pengumpulan data diperoleh melalui teknik wawancara, observasi, tes, dan dokumentasi. Data yang diperoleh pada penelitian Hasil Belajar Siswa setelah diterapkan media Teka-Teki Pintar (TTP) meningkat yaitu dapat dilihat dari hasil pratindakan siswa yaitu hanya 6 siswa (24%) mendapat nilai tuntas dan 19 siswa (76%) mendapat nilai belum tuntas. Pada siklus 1 mengalami sedikit peningkatan yaitu terdapat 15 siswa (60%) mendapat nilai tuntas dan 10 siswa (40%) mendapat nilai belum tuntas. Untuk hasil observasi aktivitas Guru pada siklus I memperoleh nilai sebesar 83,3 sedangkan hasil observasi aktivitas siswa memperoleh nilai sebesar 79,5. Pada siklus 2 juga mengalami peningkatan hasil belajar yaitu terdapat 22 siswa (88%) mendapat nilai tuntas dan 3 siswa (12%) mendapat nilai belum tuntas. Untuk hasil observasi aktivitas Guru pada siklus II memperoleh nilai sebesar 97 sedangkan hasil observasi aktivitas siswa memperoleh nilai sebesar 88,6. Dengan demikian dapat disimpulkan bahwa Penerapan Media Teka-Teki Pintar (TTP) dapat Meningkatkan Aktivitas Dan Hasil Belajar Matematika pada perkalian dan pembagian Siswa Kelas 3 SD Negeri Dringu.